2004
DOI: 10.1177/1052562903252657
|View full text |Cite
|
Sign up to set email alerts
|

Course Preparation for Management Consultants

Abstract: The explosive growth of the consulting industry in recent years and the controversy surrounding the quality of the consulting function stresses the needs for a better preparation and training of consultants. This article examines the contribution that academia can provide in furthering the development of consultants at different stages in their careers. The research indicates a scarcity of academic course offerings and a lack of comprehensive coverage of essential course elements such as client-based field pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Yet Adams and Zanzi (2004), in a comprehensive study of top-ranked U.S. business schools, suggest that there seems to be a scarcity of academic course offerings for the preparation of management consultants. In fact, a well-orchestrated professional development strategy, for full participation in management consulting practice, should take into consideration the strengths and contributions of both formal and informal learning and a review of the organization's social-cultural environment to surface contradictions between espoused priorities and actual practices (Chao, 2006).…”
Section: Parables In Pedagogymentioning
confidence: 99%
“…Yet Adams and Zanzi (2004), in a comprehensive study of top-ranked U.S. business schools, suggest that there seems to be a scarcity of academic course offerings for the preparation of management consultants. In fact, a well-orchestrated professional development strategy, for full participation in management consulting practice, should take into consideration the strengths and contributions of both formal and informal learning and a review of the organization's social-cultural environment to surface contradictions between espoused priorities and actual practices (Chao, 2006).…”
Section: Parables In Pedagogymentioning
confidence: 99%
“…The primary objective of the project is for our undergraduate MIS majors to experience first-hand the life of an MIS consultant and consultant-like IT decision making. This objective is fairly innovative, since few courses offered at top business schools train undergraduates in consulting skills [Adams and Zanzi, 2004]. The experience makes the content from the MIS course lectures and cases more real to the students, particularly those who never worked in a substantial position in any organization.…”
Section: Project Objectivesmentioning
confidence: 99%
“…IT development projects often fail to achieve their intended outcomes [Keil and Robey, 2001], many times due to a lack of alignment [Luftman et al, 1999] between the systems development project and the organizational and business process impacts of the systems implementation. Yet, few courses provide business majors with the practical experiences they need [Adams and Zanzi, 2004] to develop the expertise to avoid such failures: an understanding of what can occur in project teams and how to manage project team members, how to choose technology, how to manage organizational change, and how to write and present the typical documents used to procure technology contracts [Lee et al, 1995]. Flatly stated, most courses fail to expose students to the complex, dynamic, and unstructured situations they will face when they enter the workforce [Hernández-Serrano et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…BUSINESS COMMUNICATION (BC) is a crucial aspect of management consulting. Adams and Zanzi (2004) reported that business undergraduates, most of whom take BC courses in one form or another, are being tapped by consulting firms as "raw recruits" (p. 664).…”
mentioning
confidence: 99%
“…BC scholars have widely studied the relationship between BC and management consulting, including consulting by BC academics (Huettman, 1996;Muir, 1996;Reynolds, 1995). A limited review of the studies of management consulting, including consulting done by business college academics, hereafter referred to simply as business academics, in other business areas such as human resources (HR), marketing, and the like, showed that many of them also stressed the importance of communication skills for both business in general and management consulting in particular (Adams & Zanzi, 2004;Nord, 1996;Simon & Kumar, 2001).…”
mentioning
confidence: 99%